2017
DOI: 10.1039/c7dt03620e
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent complexes made from chelating isocyanide ligands and earth-abundant metals

Abstract: In this invited frontier article, recently discovered d and d complexes with long-lived metal-to-ligand charge transfer (MLCT) excited states are highlighted. Chelating diisocyanide ligands give access to emissive Mo(0) and Cr(0) complexes with d electron configuration exhibiting photophysical properties similar to those of Ru(ii) polypyridines or cyclometalated Ir(iii) complexes. With Ni(0), these ligands yield luminescent tetrahedral d complexes similar to isoelectronic Cu(i) bis(diimine) compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The Mo 0 diisocyanide complexes are not only emissive, but they can furthermore be employed in photoredox catalysis of thermodynamically challenging reductions, which cannot be performed with more widely known photoreductants such as fac-[Ir(ppy)3] (ppy = 2-phenylpyridine) [25]. Thus, the Mo 0 diisocyanide complexes represent Earth-abundant alternatives to precious-metal based luminophores and photoredox catalysts, and in our view, there is interesting fundamental photophysics and photochemistry to be explored in this field [26]. Recently we reported that the [Mo(L tBu )3] complex exhibits much more favorable photophysical properties than the closely related [Mo(L Me )3] compound, and we demonstrated that [Mo(L tBu )3] is more widely applicable in photoredox catalysis due to greater photo-robustness [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mo 0 diisocyanide complexes are not only emissive, but they can furthermore be employed in photoredox catalysis of thermodynamically challenging reductions, which cannot be performed with more widely known photoreductants such as fac-[Ir(ppy)3] (ppy = 2-phenylpyridine) [25]. Thus, the Mo 0 diisocyanide complexes represent Earth-abundant alternatives to precious-metal based luminophores and photoredox catalysts, and in our view, there is interesting fundamental photophysics and photochemistry to be explored in this field [26]. Recently we reported that the [Mo(L tBu )3] complex exhibits much more favorable photophysical properties than the closely related [Mo(L Me )3] compound, and we demonstrated that [Mo(L tBu )3] is more widely applicable in photoredox catalysis due to greater photo-robustness [27].…”
Section: Introductionmentioning
confidence: 99%
“…The Mo 0 diisocyanide complexes are not only emissive, but they can furthermore be employed in photoredox catalysis of thermodynamically challenging reductions, which cannot be performed with more widely known photoreductants such as fac-[Ir(ppy) 3 ] (ppy = 2-phenylpyridine) [25]. Thus, the Mo 0 diisocyanide complexes represent Earth-abundant alternatives to precious-metal based luminophores and photoredox catalysts, and in our view, there is interesting fundamental photophysics and photochemistry to be explored in this field [26].Inorganics 2020, 8, x FOR PEER REVIEW 2 of 11…”
mentioning
confidence: 99%
“…MLCT excited state,63 a design principle that was inspired by the well-known [Cu(dpp)2] + complex(Figure 6a).42 Nevertheless, these Ni(0) complexes are only luminescent well below room temperature(Table 3).…”
mentioning
confidence: 99%
“…The next publication on luminescent Ni(0) complexes appeared in 2017 after a break of 14 years, when we reported on two homoleptic complexes with bidentate isocyanide ligands (Scheme 3a/b) [28]. We had previously discovered that such chelating isocyanides provide access to relatively robust d 6 metal complexes made from Cr(0) and Mo(0) that are luminescent analogues of well-known Ru(II) polypyridyl and cyclometalated Ir(III) complexes [34][35][36][37][38]. The molecular design of the Ni(0) complexes in Scheme 3a/b was inspired by the structure of the Cu(dpp)2 + parent complex (dpp = 2,9-diphenyl-1,10-phenanthroline), in which the phenyl-substituents in -position to the ligating N-atoms are used to impede planarization in the MLCT state, thereby enhancing the luminescence properties [1,5].…”
Section: From Early Structural Studies To Emissive Complexesmentioning
confidence: 99%